Volume of verse: wandering through water - Rachbuch, Shelley Ann. (My University, 2006)
This thesis comprises a volume of verse entitled ‘Wandering through water’ and a theoretical reflection on it. The volume contains poems written, edited and refined over the two year research period (July 2003 to May 2005). A reflexive essay accompanies it, providing a template for an account of the poems’ composition and a description of poetic devices and practices employed. It also engages with the primary concerns of the verse and its possibilities. The essay reflects on the working method employed: the process and necessity of refining a poem by tracing its multiple revisions. Reflexive tools utilized in this ‘mapping’, include the ‘Writer’s Reflexive Journal’, suggestions and comments made during supervision and workshop processes, as well as engagement with other poet’s work. The reflexive essay also explores that the thematic priorities of the poetry and its inspiration which is rooted in a historical, Jewish and South African context. In the space of the poetry it is re-narrated, negotiated and struggled with and at times experienced without the mediation of conscious thought, to produce alternative meaning and the possibility of selfhood. It explores the responsibilities of a poet to her community. Further, that the writing of poetry contains within it the possibility of extending that which is personal and contextualised into a spiritual or universal experience.
Faculty of Humanities School of Literature and Language Studies 8707325r sheileya@myconnection.co.za
Keywords: water; poems; devices; processes; Jewish